REALISME MAGIS DALAM NOVEL SIMPLE MIRACLE DOA DAN ARWAH KARYA AYU UTAMI - Sandra Whilla Mulia (Lakon : Jurnal Kajian Sastra dan Budaya, 2016)
This study are intend to reach some goals. First, this aimed to uncover the magic realism which is narrated in Ayu Utami’s novel, entitled Simple Miracle DoaDan Arwah. Second, this study aimed to discover socio cultural context which form the background of the emerging of magic realism of narrative in Ayu Utami’s novel entitled Simple Miracle Doa dan Arwah. This research utilizes magic realism narrative theory on the book Ordinary Enchantments Magical Realism andRemystifiction of Narratives written by Wendy B. Faris (2004). This is a qualitative study which employed textual analysis to analyze the obtained data. The results of 2 this study were magic realism which was narrated in the novel were not only loaded by the characteristics of Faris’ magic realism by showing the exquisite existence of myth in this modern era, but also written to be in charge of bracing and reorganizing people’s believe in Javanese myth. Socio cultural context which form the background of the emerging of this novel was Javanese culture that still exist in this modern era. This was also added by the comeback of traditional ambience which made its existence popular nowadays. From the analysis this had emerged two issues, social issues and signification issues. The emerging social issues are the Javanese culture in which the people tend to fancy mystics. These mystics are related to ghosts. In addition, the other issue is about acculturation of religions in Java Island. Besides the issues, the signification obtained were: (1) Javanese will always hold their believe in ghost; (2) in Java, shaman and spirits or ghost are correlated to the second alternative to realize dreams; (3) shaman identity is identical with someone who has an ability to see and communicate with spirits or ghosts; (4) there is a believe that spirits and ghosts are everywhere; (5) Javanese believe that every dead person will soon become spirits and ghosts and they will eternally live around them; (6) atheist will rarely be seen in Java; (7) religions in Java Island will always blend themselves with the culture.